Revisiting the global food architecture: Lessons from the 2008 food crisis - Luc Christiaensen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
The 2008 episode of food price explosion, political turmoil, and human suffering revealed important flaws in the current global food architecture. This paper argues that to safeguard the strengths of the current system, four failures in market functioning and policymaking must be addressed. First, governments must reinvest in agriculture with a focus on public goods and subject to increased public accountability to re-ensure the global food supply. Second, the policy-induced link between food and fuel prices must be broken through a revision of EU and US agro-fuel policies. Third, better sharing of information on food stocks, stricter WTO regulation of export restrictions, and some form of globally managed buffer stock will be minimum requirements to prevent the resurgence of inefficient national food self-sufficiency policies. Fourth, a market-based food security system is only sustainable given well functioning national social safety nets.
Keywords: Q18; 330; Agriculture; agro-fuels; food crisis; food security; Landwirtschaft; Biokraftstoff; Ernährungssicherung; Welt